2016
DOI: 10.1016/j.chom.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Acinetobacter baumannii to Zinc Starvation

Abstract: Summary Zinc (Zn) is an essential metal that vertebrates sequester from pathogens to protect against infection. Investigating the opportunistic pathogen Acinetobacter baumannii’s response to Zn starvation, we identified a putative Zn metallochaperone, ZigA, which binds Zn, is required for bacterial growth under Zn-limiting conditions, and for disseminated infection in mice. ZigA is encoded adjacent to the histidine (His) utilization (Hut) system. The His ammonia-lyase HutH, binds Zn very tightly only in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
173
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(179 citation statements)
references
References 39 publications
5
173
1
Order By: Relevance
“…Multiple studies conducted by prominent laboratories have demonstrated that iron or zinc limitation can suppress Acinetobacter growth and that the organisms have multiple iron and zinc acquisition mechanisms, including catechol production, production of very high-affinity siderophores (e.g., acinetobactin) and companion siderophore uptake receptor and energetic mechanisms, and heme utilization (82,121,(308)(309)(310)(311)(312)(313)(314)(315)(316)(317)(318)(319)(320). Small-molecule iron chelators have in vitro activity at killing Acinetobacter during log growth (318).…”
Section: Trace Metal Sequestrationmentioning
confidence: 99%
“…Multiple studies conducted by prominent laboratories have demonstrated that iron or zinc limitation can suppress Acinetobacter growth and that the organisms have multiple iron and zinc acquisition mechanisms, including catechol production, production of very high-affinity siderophores (e.g., acinetobactin) and companion siderophore uptake receptor and energetic mechanisms, and heme utilization (82,121,(308)(309)(310)(311)(312)(313)(314)(315)(316)(317)(318)(319)(320). Small-molecule iron chelators have in vitro activity at killing Acinetobacter during log growth (318).…”
Section: Trace Metal Sequestrationmentioning
confidence: 99%
“…More recently, other transporters have been shown to function in Zn uptake in S. enterica and Vibrio cholera (40,41). As discussed above, host strategies to limit bacterial infection exploit both zinc toxicity, perhaps best understood for intracellular niches (3,42), and severe zinc limitation (starvation) (43).…”
Section: Zinc Efflux and Acquisitionmentioning
confidence: 99%
“…The metal-free metallophore is proposed to be exported through CntE, a major facilitator superfamily (MFS) transporter, and then imported as the metallated complex via a specific ABC transporter, CntABCDF. B, model of how histidine uptake and catabolism impact the labile histidine-Zn pool in A. baumannii under conditions of host-mediated Zn starvation (43). His is proposed to be taken up as His 2 -Zn complex through HutT.…”
Section: Zinc Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…We also amplified the isolated fepA gene using the same strategy. Following digestion, we ligated these two PCR products into pWH1266 or p2682pro (81) to make pAbafepA and p2682proAbafepA, respectively. For each construct, we confirmed the sequences of the promoter, terminator, and structural gene (McLab, San Francisco, CA).…”
Section: Methodsmentioning
confidence: 99%